EFEKTIVITAS KEBIJAKAN SERTIFIKASI GURU SD DALAM MENDORONG TRANSFORMASI PENDIDIKAN DASAR BERKUALITAS - Ananda, Rizki; Nadira, Vonny; Arianti, Nelvi; Al-Fikamza, Marvina; Sayuti, Amlan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Quality primary education serves as a fundamental pillar in developing competent human resources. One of the Indonesian government's strategic policies to ensure educational equity is the implementation of teacher certification programs at the elementary school level, aimed at enhancing teachers' professional competence as agents of instructional transformation. This study seeks to evaluate the effectiveness of the elementary school teacher certification policy in improving learning quality and promoting transformation in basic education. Employing a qualitative method through a literature review approach, this research examines academic articles, policy reports, and scholarly literature from the past decade. The findings reveal that while certification enhances teacher motivation and professional recognition, its impact on instructional practices and student learning outcomes remains limited. Certification tends to be administrative in nature and is not yet fully integrated with continuous professional development initiatives. This study contributes to educational policy discourse by offering critical insights into the need for redesigning performance-based certification systems and reinforcing post-certification training as part of a more equitable and quality-driven basic education reform.